Influence of Molecular Parameters on Rate Constants of Thermal Dissociation/Recombination Reactions: The Reaction System CF4 ⇄ CF3 + F - Cobos, Carlos Jorge (2023)
The possibilities to extract incompletely characterized molecular parameters from experimental thermal rate constants for dissociation and recombination reactions are explored. The reaction system CF4 (+M) ⇄ CF3 + F (+M) is chosen as a representative example. A set of falloff curves is constructed and compared with the available experimental database. Agreement is achieved by minor (unfortunately not separable) adjustments of reaction enthalpy and collisional energy transfer parameters.